Pengaruh Shift Kerja Terhadap Tingkat Kelelahan Tenaga Kerja Bagian Packing di PT Air Mancur, Wonogiri - Meita Nur Khasanah; Siti Hani Istiqomah; Lilik Hendrarini (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
Working in shift is an alternative for organizing work-load and is created because of the need in maximizing productivity for fulfilling consumers demands. One of the healthy drinking industries which are applying work-shift is PT Air Mancur which s located in Wonogiri. Based on a preli-minary survey conducted in packing division of the company, some complaint related with work fatigue were found among the workers. The study was aimed to know the influence of work-shifts on work fatigue and to know, as well, which shift has the biggest effect, by conducting a cross sectional survey. From 127 workers as the study population, 97 people were selected as the sample, and were randomized proportionally into three different work-shifts. The fatigue was me-asured by reaction timer and the data collected were analysed by using one way anava and LSD test at 95 % level of significance. The results of the study showed that in the morning and after-noon shifts, work fatigue in moderate level were occured in most workers (78,1 % and 93,7 % respectively), meanwhile in the night shift, all workers were experiencing heavy levelled fatigue. The subsequent statistical test confirmed that the difference of fatigue level among the three shifts were significant and the night shift had the biggest influence. Based on the results, the company is advised to give breaktime for workers to have relaxation, to control temperature of work environment, and to provide extra meal for night shift workers. On the other hand, night shift workers were suggested to manage their sleeping time and to spare some times for resting sufficiently.